Shear strength and crushing characteristics of calcareous sand in South China Sea under the influence of three factors - Jianfeng ZHU; Ting LI; Luying JU; Hao YANG (Shuiwen dizhi gongcheng dizhi)
Calcareous sand, a type of marine soil found in the South China Sea, is characterized by its porous nature, irregular particle shape, and susceptibility to breakage. However, few studies have examined the mechanical properties of calcareous sand from the microscopic perspective. To investigate the impact of vertical pressure , shear degree and relative density on the strength and particle breakage characteristics of calcareous sand, direct shear tests were conducted on saturated calcareous sand from the South China Sea. A comparative analysis was performed with the test results of terrestrial silica sand, namely Chinese standard sand and Fujian intermediate sand. It is found that both the trend of stress-displacement curve and the peak shear stress values exhibit a similar behavior for calcareous sand under different relative compaction, which were distinctly different from the influence of relative compaction on Chinese standard sand and Fujian intermediate sand. The calcareous sand in the South China Sea exhibit a noteworthy “similar cohesion”, a feature that distinguishes it from the non-cohesiveness of terrigenous silica sand. This cohesion in calcareous sand is attributed to the non-uniform shape of its particles and featuring interlocking between particles, presenting certain bonding characteristics.As the vertical stress increases, the crushing of calcareous sand gradually changes from large particles to small particles. At a shear degree approaching 50%, the crushing surface of calcareous sand occurs mainly at a relatively weak position. However, at the shear degree approaching 100%, the primary crushing surface predominantly occurrs in the middle of individual calcareous sand particles. The relative breaking potential demonstrates a strong correlation with vertical stress, relative compaction, and shear degree. The developed empirical model for breaking potential, which takes all three factors into account, holds significant potential for practical applications in engineering. The findings provide valuable insights for the construction of islands and reefs in the South China Sea.